2012
DOI: 10.2118/129907-pa
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Soluble, Nonionic, Water-Soluble Surfactants That Stabilize CO2-in-Brine Foams

Abstract: Several commercially available and a few experimental, nonionic surfactants were identified that are capable of dissolving in carbon dioxide (CO 2 ) in dilute concentration at typical minimum-miscibility-pressure (MMP) conditions and, upon mixing with brine in a high-pressure windowed cell, stabilizing CO 2 -in-brine foams. These slightly CO 2 -soluble, water-soluble surfactants include branched alkylphenol ethoxylates, branched alkyl ethoxylates, a fatty-acid-based surfactant, and a predominantly linear ethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
60
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 34 publications
5
60
0
3
Order By: Relevance
“…Sagir et al (2014c, d) conducted pure CO 2 injection after surfactant solution flooding to mimic FAWAG with a new CO 2 -soluble surfactant using Berea cores, during which a mobility reduction factor of 3.1 was achieved. Similar results were demonstrated by Xing et al (2012) and McLendon et al (2014) relative to pure CO 2 injection on carbonate and sandstone cores. Recently, 80 cP of foam apparent viscosity was achieved by Chen et al (2015) in a 49-mD dolomite core with a switchable ethoxylated cationic CO 2 -philic surfactant.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Sagir et al (2014c, d) conducted pure CO 2 injection after surfactant solution flooding to mimic FAWAG with a new CO 2 -soluble surfactant using Berea cores, during which a mobility reduction factor of 3.1 was achieved. Similar results were demonstrated by Xing et al (2012) and McLendon et al (2014) relative to pure CO 2 injection on carbonate and sandstone cores. Recently, 80 cP of foam apparent viscosity was achieved by Chen et al (2015) in a 49-mD dolomite core with a switchable ethoxylated cationic CO 2 -philic surfactant.…”
Section: Introductionsupporting
confidence: 81%
“…Similar to WAGS, this method improves in situ foam generation, drastically lowers the injection costs, and reduces the loss of surfactant onto the rock surface due to adsorption. Xing et al (2012) and McLendon et al (2014) showed that the mobility reduction factor was around two, which was slightly higher than pure CO 2 injection on pre-saturated cores. In Le et al (2008), experimental and field scale simulation results show this is the most promising injection scenario which gave highest oil recovery and injectivity.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations